2018
DOI: 10.1080/15405702.2017.1412440
|View full text |Cite
|
Sign up to set email alerts
|

Does the subaltern speak? Migrant voices in digital Europe

Abstract: This article examines a number of digital initiatives where refugees and migrants speak with/to Europe in the context of the "migration crisis". The analysis of four institutional and grassroots initiatives illustrates digital Europe's symbolic articulations of borders that divide people and territories. As argued, the mediated visibility and voice of refugees and migrants matters precisely as the order of appearance (Arendt, 1958) in digital Europe represents a fundamental dimension of the continent's communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…On the other side of the divide, literature on migration and the media has identified, what we call, the symbolic border both in the networked stories and voices of migration produced and circulated through digital technologies (Georgiou, 2018; Leurs and Smets, 2018) and in the journalistic narratives about migration that continue to shape public conversations about human mobility in Europe (Berry et al, 2015; Musarò, 2018; Tyyskä et al, 2018). Literature on digital technologies, to begin with, focuses on the use of smartphones and social media platforms in ‘crisis’ contexts so as to explore the potential of such personalised technologies to shift the power relations of the border.…”
Section: Defining the Border: Power Territory And Narrativementioning
confidence: 99%
“…On the other side of the divide, literature on migration and the media has identified, what we call, the symbolic border both in the networked stories and voices of migration produced and circulated through digital technologies (Georgiou, 2018; Leurs and Smets, 2018) and in the journalistic narratives about migration that continue to shape public conversations about human mobility in Europe (Berry et al, 2015; Musarò, 2018; Tyyskä et al, 2018). Literature on digital technologies, to begin with, focuses on the use of smartphones and social media platforms in ‘crisis’ contexts so as to explore the potential of such personalised technologies to shift the power relations of the border.…”
Section: Defining the Border: Power Territory And Narrativementioning
confidence: 99%
“…Myria Georgiou in her assessment of digital migrant voices in Europe also finds that ‘voice does not guarantee recognition’. She argues on the basis of an analysis of two institutional and two grassroots migrant digital initiatives that while some are ‘challenging hegemonic structures’, most are ‘digitally reaffirming bordering power’ (Georgiou, 2018: 45). In her quantitative analysis of news on refugees in the United Kingdom and the United States, Roopika Risam (2018) found that refugees’ selfies (not news photographs of refugees taking selfies) allow subjects to ‘avoid co-optation’ in stereotypical one-sided narratives (p. 58).…”
Section: Migrants’ Narrativesmentioning
confidence: 99%
“…But this right to speak is itself embedded in specific power relations. Indeed, those who have succeeded in exerting it are ‘selective voices’ who ‘hold a certain symbolic capital’ (Georgiou, 2018: 45, 54).…”
Section: Online Alternative Media Representations?mentioning
confidence: 99%